Insertion of amelogenin marker in the 38 Hid-Indels multiplex reaction - Braganholi, D. F. [UNESP]; Polverari, F. S. [UNESP]; Ambrosio, I. B. [UNESP]; Cicarelli, R. M.B. [UNESP] (Elsevier, 2015)
Pereira et al. [3] reported a method for multiplex analysis of 38 INDELs autosomes known polymorphic in different populations of the world which can be used in the human identification, but this methodology not originally introduced marker for the analysis of amelogenin. In laboratory of paternity of UNESP/Araraquara, Brazil, kinship analysis are performed using samples with degraded DNA, where the amplification of 38HID-INDELs was efficient compared to STRs in these samples. For paternity tests also analyze STRs, and the verification of the sex of samples is done by the amelogenin marker analysis present in commercial kits, but the bad ampification of STRs may interfere in the correct reading of amelogenin in the electropherogram. Trying to solve this problem we decided to add the amelogenin marker in multiplex reaction with 38HID-INDELs.
Keywords: Amelogenin marker; Degraded DNA; INDELs